2016
DOI: 10.1002/jsfa.8053
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of peptides from common bean protein isolates and their potential to inhibit markers of type‐2 diabetes, hypertension and oxidative stress

Abstract: Peptides from common bean have antidiabetic and antihypertensive potential regardless of their antioxidant capacity. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 44 publications
3
70
0
Order By: Relevance
“…The antioxidant activity was also observed in peptides with less than 20 amino acid residues per molecule, because these small peptides have a better ability to cross the intestinal barrier and exert their biological effects . Finally, peptides with hydrophobicity ≤20 kcal mol −1 are more effective for penetrating the cell membrane and to exercise effects on the molecule . Interestingly, most of the peptides found in DTP and digested protein fractions from chia seed showed these characteristics, which may explain the benefits found in the present study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The antioxidant activity was also observed in peptides with less than 20 amino acid residues per molecule, because these small peptides have a better ability to cross the intestinal barrier and exert their biological effects . Finally, peptides with hydrophobicity ≤20 kcal mol −1 are more effective for penetrating the cell membrane and to exercise effects on the molecule . Interestingly, most of the peptides found in DTP and digested protein fractions from chia seed showed these characteristics, which may explain the benefits found in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…[53] Finally, peptides with hydrophobicity ࣘ20 kcal mol −1 are more effective for penetrating the cell membrane and to exercise effects on the molecule. [54] Interestingly, most of the peptides found in DTP and digested protein fractions from chia seed showed these characteristics, [14,32] which may explain the benefits found in the present study.…”
Section: Discussionmentioning
confidence: 58%
“…Due to the enzyme's central role in regulating postprandial glucose release, α-glucosidase inhibitors have been developed for type 2 diabetes management. The presence of hydrophobic amino acids Pro, Met and Ala, close to the C-terminal of the peptide, was observed to contribute in promoting the inhibitory activity (Kang et al, 2013;Mojica et al, 2017). Molecular docking studies also revealed that hydrophobic amino acid residues of peptides predominantly interact with residues in the active site of α-glucosidase (Mojica and de Mejía, 2016;Di Stefano et al, 2018).…”
Section: Alpha-glucosidase Inhibitionmentioning
confidence: 99%
“…Therefore, besides attempting to increase the potency of food protein hydrolysates/peptides, the search for peptides having multiple bioactivities is of particular interest. In this context, hydrolysates and peptides displaying a range of in vitro bioactivities including other antidiabetic (e.g., α‐glucosidase inhibition), antioxidant, and antihypertensive effects have been described in the literature (Connolly, Piggott, & FitzGerald, ; Harnedy & FitzGerald, ; Lacroix, Meng, Cheung, & Li‐Chan, ; Mojica, Luna‐Vital, & González de Mejía, ; Neves, Harnedy, & FitzGerald, ; Nongonierma & FitzGerald, ; T.‐Y. Wang, Hsieh, et al, ; C. Zhang, Zhang, Wang, Chen, & Luo, ). Potent DPP‐IV inhibitory peptides have been identified in several food protein‐derived hydrolysates.…”
Section: Future Directionsmentioning
confidence: 99%